Faktor-Faktor Yang Berhubungan Dengan Kejadian Acne Vulgaris Pada Remaja: Health Promotion Perspective at SMA Budi Mulia Utama - Salsabila, Yuki Aliya; Safrudin, Safrudin; Rajab, Wahyudin (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Background: According to data from the World Health Organization (WHO), approximately 85% of adolescents worldwide experience acne with varying degrees of severity. Based on a study from the Global Burden of Disease (GBD), the occurrence of Acne Vulgaris begins at puberty and reaches 85% in the age range of 12–15 years, with its peak between the ages of 15–17 years. Acne Vulgaris affects 90% of males and 80% of females across various ethnicities worldwide. Objective: This study aims to determine the factors influencing the incidence of Acne Vulgaris among adolescents at SMA Budi Mulia Utama from a health promotion perspective. Research Method: This study used a quantitative approach with a cross-sectional design and a total sample of 85 respondents. Data analysis was conducted using validity tests, reliability tests, chi-square, and risk estimate. Research Results: Poor dietary patterns, high stress levels, low personal hygiene, and poor sleep quality were significantly associated with the incidence of Acne Vulgaris (p<0.05). Conclusion: There is a significant relationship between dietary patterns, stress levels, personal hygiene, and sleep quality with the incidence of Acne Vulgaris among adolescents at SMA Budi Mulia Utama.